2024
DOI: 10.4314/sajas.v53i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriolytic activity of ruminal protozoa is affected by rate and type of common essential oils: Effect of thyme oil

Z. Sahan

Abstract: Over the past two decades, research into the effects of essential oils (EOs) on rumen microorganisms as an alternative to antibiotics has  intensified. Yet, there are few investigations on rumen protozoa. To evaluate if EOs have antiprotozoal efficacy against rumen protozoa,  the present investigation was conducted. Using the potentiality of rumen protozoa to digest 14C-labeled bacteria, the influence of EOs on  in vitro protozoal activity was determined. For the study, orange peel, cinnamon, laurel, oleaster,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The abundance of total bacteria in batch cultures, as well as that of protozoa and F. succinogenes in the rumen of steers, were adversely affected by the use of cinnamon EO containing between 57% and 70% of CIN [50,51]. Although these results partially agree with those of the present study, Khorrami et al [49] also reported that supplementing the diet of steers with CIN (5.7 g of cinnamon essential oil/d) decreased the relative abundance of archaea in the rumen. As cinnamon essential oil contains other compounds besides CIN, their combination might have a synergistic effect on certain microbial populations.…”
Section: Cinnamaldehydesupporting
confidence: 90%
See 1 more Smart Citation
“…The abundance of total bacteria in batch cultures, as well as that of protozoa and F. succinogenes in the rumen of steers, were adversely affected by the use of cinnamon EO containing between 57% and 70% of CIN [50,51]. Although these results partially agree with those of the present study, Khorrami et al [49] also reported that supplementing the diet of steers with CIN (5.7 g of cinnamon essential oil/d) decreased the relative abundance of archaea in the rumen. As cinnamon essential oil contains other compounds besides CIN, their combination might have a synergistic effect on certain microbial populations.…”
Section: Cinnamaldehydesupporting
confidence: 90%
“…Moreover, Chapman et al [17] observed a reduction in urinary urea N and total purine derivatives after supplementing the diet of dairy cows with 2 mg/kg of BW, without another effect on milk performance and rumen fermentation parameters. Although the effect of CIN on nitrogen metabolism in the rumen is difficult to explain, Sahan [49] studied the influence of cinnamon essential oil on in vitro protozoal activity, determined by the potentiality of rumen protozoa to digest 14C-labeled bacteria, and he observed a lower degradation of bacterial by protozoa after adding a dose of 5000 mg/kg of cinnamon essential oil. The results of this study suggest that CIN supplementation may increase the supply of microbial protein to the host animal, which is a positive and very interesting result.…”
Section: Cinnamaldehydementioning
confidence: 99%